No long-term complications after pulmonary embolism in an infant with multiple risk factors - Kołodziejczak, Michalina; Kołodziejczak, Michał (Pediatria Polska - Polish Journal of Paediatrics, 2021)
Pulmonary embolism (PE) in the paediatric population is rare and is characterised by unspecific presentation, misdiagnosis, and high mortality rates. An unusual case of pulmonary embolism in an infant with lower extremity plaster splints due to congenital clubfoot is presented. A male infant, 1.5 months old, was hospitalized due to otitis and suspicion of congenital heart disease. Generalized cyanosis with simultaneous saturation drops occurred only during physical effort. The clinical presentation represented the features of PE in the course of lower limb thrombosis, which were confirmed by laboratory tests and chest angio-CT. The diagnosis was amended, and heparin was administered, which resulted in a gradual, systematic improvement of the clinical condition. In a follow-up diagnosis, gene mutation of factor V Leiden was found. During 13 years of follow-up no recurrent thrombotic events were observed.